Faber’s Maple: Acer fabri - Gary W. Knox (EDIS)
Faber's Maple is unlike the maples familiar to most people, as it does not have the typical three- or five-lobed leaves. Instead, the leaves of Faber's maple are unlobed, slender, and very glossy. Additionally, most people know the maple as a deciduous tree, dropping its leaves in fall, whereas Faber's maple is evergreen. This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, December 2013.